Perbandingan Hambatan Implementasi Resep Elektronik di Berbagai Fasilitas Pelayanan Kesehatan: Sebuah Tinjauan Sistematis - Yusup Maulana; Susi Ari Kristina; Chairun Wiedyaningsih (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Electronic prescribing (e-prescribing) is increasingly implemented to improve patient safety and healthcare efficiency. However, its implementation across different healthcare settings continues to face complex and varied barriers. Aim: This systematic review aims to identify barriers to e-prescribing implementation, compare variations in barriers across healthcare facility types, and develop evidence-based recommendations. Methods: A systematic literature search was conducted in Scopus, PubMed, and ScienceDirect following PRISMA guidelines, supplemented by manual reference screening and grey literature searches. Eligible studies included English-language qualitative and mixed-methods research focusing on implementation barriers. Data were analyzed using thematic synthesis, while methodological quality was assessed using the Joanna Briggs Institute (JBI) tools and the Mixed Methods Appraisal Tool (MMAT). Results: Ten studies met the inclusion criteria, covering hospitals, primary care clinics, community pharmacies, and residential aged care facilities. Four major categories of barriers were identified: technical and system challenges, workflow barriers, human and behavioral factors, and organizational and regulatory constraints. Barrier patterns varied significantly across facility types, with technical barriers being most dominant in hospitals, transitional barriers in primary clinics, operational pressures in pharmacies, and low user motivation in residential aged care facilities. Conclusion: Successful e-prescribing implementation requires an integrated approach addressing technical, organizational, and human factors. Implementation strategies must be tailored to the specific characteristics of each healthcare setting to support patient safety and sustainable healthcare quality.